OLIY TA'LIMDA “RADIATSION TIBBIYOT VA TEXNOLOGIYALAR” FANINING SAMARADORLIGINI OSHIRISHDA “HAMKORLIKDA” O‘QITISH TEXNOLOGIYASIDAN FOYDALANISH - Bozorov, Е.Х.; Zoirova, L.X. (SCIENCE and SOCIETY, 2022)
This article explains in detail the use of "Collaborative" teaching technology in the classroom on the example of "Application of radiation medicine and technology in health care." The results and benefits of using this method are also listed.
Keywords: radiation medicine and technology; “Collaborative” teaching technology; health; science and technology development; modern interactive methods; skills; teamwork; active participation